The Role of Panoramic Radiographs in Determining The Preprosthetic Treatment During Denture Fabrication - A Case Report - Ivony Fitria; Gunawan Gunawan (Faculty of Dentistry Universitas Andalas, 2022)
Background: The success of a removable denture can be determined by the good support of the mucosa and alveolar bone that underlies a denture. Visually and tactilely in the oral examination could not provide adequate information about the condition of the tissue under the submucosa. A panoramic radiograph can show anatomical considerations that influence the fabrication of a removable denture. Therefore, a panoramic radiograph of the patient can help reveal anomalous or pathological conditions in the patient's oral cavity. Purpose: To describe the importances of panoramic radiograph to identify lesions that are not clinically visible in the oral. Case: This article reports a patient with complaints of discomfort in the previous denture. On clinical examination found a prominance on the lower jaw in the left side of the mandible and it was pain on palpation. The patient was referred to radiology for a panoramic radiograph. From this panoramic radiograph, a suspected complex odontoma was found in the lower left posterior region. The patient was immediately referred to the Oral Surgery department for surgery. Conclusion: Panoramic radiographs play an important role in helping to establish a diagnosis of tissue that is not visible during clinical examination. This case demonstrates that with the aid of radiology, a preprosthetic treatment plan can be established to prepare the supporting tissue for removable dentures.